Diversity of decapod crabs (Crustacea: Brachyura) in two islands of Ubatuba, southeast of Brazil - Godoy, Amanda Thaís [UNESP]; de Sousa, Aline Nonato [UNESP]; Bernardo, Camila Hipolito [UNESP]; Bernardes, Veronica Pereira [UNESP]; Reis, Danielle Monique [UNESP]; Fransozo, Adilson [UNESP] (Springer Nature, 2020)
This is the first comparative study of the alpha and beta diversity of crabs from soft bottom areas nearby two coastal islands (Couves and Mar Virado Islands). Crabs were captured monthly from January 1998 to December 1999. The samplings were carried out with a shrimp fishery boat provided with double-rig nets within a marine protected area in Ubatuba off the north coast of São Paulo. The ecological indexes of diversity (H′), equitability (J′) and β-diversity were used to compare the variation in diversity between islands and years. In total, we captured 2221 brachyurans (570 in Couves and 1651 in Mar Virado), belonging to 42 species, 28 genera, and 13 families. Twenty species occurred in both islands, ten occurred only in Couves, and 12 were exclusive of Mar Virado. The three most abundant species were Callinectes ornatus, Hexapanopeus paulensis, and Hepatus pudibundus. There were statistical differences in equitability (between islands in the year of 1998) and abundance (among seasons in the autumn of 1999) (p < 0.05). Although the two islands are geographically close to each other, they have distinct environmental features. Couves Island, for instance, is more affected by the water masses reaching Ubatuba than Mar Virado Island. These characteristics are probably driving the community composition of these islands.
Keywords: Benthonic assemblages; Brachyura; Community structure; Richness; Spatiotemporal diversity